Assessing Country Progress Towards Digitization - Melhem, Samia (Washington, DC: World Bank, 2019)
Today, almost all developing nations’ public administrations are going digital, leveraging disruptive technologies for better service delivery and improved efficiency. The question countries ask most frequently is where do we start?, and while the answer may seem daunting, the key to success is not where to start, but how to sustain what has most certainly already started.